Inuit Self-determination and Postsecondary Education: The Case of Nunavut and Greenland - Gaviria, Olga
With Inuit identifying as a people beyond nation-state boundaries, and Nunavummiut and Greenlanders as citizens of Canada and Denmark, the right to self-determination has followed distinct trajectories in the jurisdictions examined in my thesis. Nunavut has a constitutional mandate to be responsive to the Nunavut Land Claims Agreement, paradoxically intensifying the relationships with the federal government towards further devolution and maintaining an ethnic divide trespassing territorial lines. Envisioning statehood, Greenland has chosen to gradually break economic ties with Denmark and in mainstreaming its governance capacity it appears to be branching off ethnocentric policies. In what seem opposing pathways, autonomous postsecondary education institutions are positioned to mitigate the notional extremes the right to self-determination calls upon. By comparing institutions steering through conflicting missions, this thesis illustrates the ways in which the right to self-determination operates against the backdrop of regained geopolitical prominence of the Arctic Region. Applying a legal theoretical framework to the scholarship of indigenous education this thesis raises a number of issues in carrying forward the right to self-determination once indigenous peoples regain control over their destinies. Issues regarding social stratification challenging the politics of representation indicate that achieving some form of autonomy does not necessarily result in social justice as the indigenous rights advocacy scholarship suggests. Considering the Inuit right to self-determination as a process right rather than an outcome, this finding highlights internal pluralities challenging the reification of Inuit identity on the basis of cultural, political, and socioeconomic difference. This thesis advocates for examining the contingencies that shape Inuit multiple allegiances accounting for peoples vantage geopolitical positioning. As Inuit redefine their position in the local, national, and global spheres, important knowledge is produced overcoming the single overriding of identity politics. Recognizing that Inuit knowledge is knowledge in context, the author contends, may lead to new ways for postsecondary education to uphold the Inuit right to self-determination. PhD